H-reflex excitability in children with spastic cerebral palsy - Mahmud, Ahmed S.; Alwan, Basim M.; Mezaal, Mohammad A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Cerebral palsy is a disorder of movement and posture resulting from permanent, nonprogressive defect or lesion of the immature brain. Spastic cerebral palsy is a common clinical type which is difficult to diagnose clinically in the early years of life. This study was conducted to identify the changes in the H-reflex excitability in children with spastic cerebral palsy as compared to normal children. Methods: The excitability of the monosynaptic H-reflex pathway was tested in 36 children with spastic cerebral palsy during waking by calculation of the H-reflex wave amplitude with the ratio of maximal H /maximal M response amplitudes and compared with 32 normal children of the matching age. The Hoffman’s reflex was evoked in the soleus muscle after stimulation of the tibial nerve at the popliteal fossa. Results: The mean H-reflex wave amplitude (Ha) values are found to have statistical significant difference between both groups (P <0.05) while the mean maximum M-response amplitude (Ma) showed no statistical differences between both groups (P>0.05). However, the ratio of mean amplitude of the maximum H-wave to that of the maximum M-response (Ha/Ma) was significantly higher in the spastic children group than in controls (P <0.05). Conclusion: Our results showed that the Ha/Ma ratio does provide a helpful electrophysiological tool that can be correlated with the other clinical signs in the diagnosis of cerebral palsy by identifying motor neuron hyperexcitability.